Cone beam computed tomography and histological evaluations of a straight electrode array positioning in temporal bones. (4th March 2017) - Mosnier, Isabelle; Célérier, Charlotte; Bensimon, Jean-Loup; de Seta, Daniele; Sterkers, Olivier; Nguyen, Yann; Bernardeschi, Daniele
Abstract: Conclusion: CBCT allows a precise evaluation of the dimensions and of the shape of the cochlear duct that is of primary importance for the choice of the length and the design of the electrode array. This radio-histological study confirms that CBCT is a reliable tool to be used in clinical studies to evaluate the position of straight electrode arrays within the cochlear scala. Objective: To validate the reliability of cone beam computed tomography (CBCT) in the evaluation of cochlear anatomy and positioning of a straight electrode array, by comparing radiological images to histological analysis of cochlear implanted temporal bones. Methods: Eight temporal bones for four subjects were analysed before and after cochlear implantation with a straight electrode array. The size of the cochlea, the dimensions, and shape of the cochlear duct at 180° and 360° were evaluated on CBCT performed before implantation. Temporal bones then underwent histological analysis to determine the position of the electrode array. Scalar localization of the electrode array was assessed on CBCT performed after implantation, and compared with histological study. Results: CBCT is a reliable radiological technique to differentiate variability not only of cochlear dimensions, but also of size and shape of the cochlea. Histological analysis confirmed the scalar position of the electrode array assessed by the CBCT in 7/8 temporal bones, but soft tissue trauma such as dissection of the spiral ligament was not identified by the CBCT.